Pengaruh Model Project Based Learning Berbasis Ecopreneurship terhadap Literasi Lingkungan & Eco-anxiety Pada Materi Perubahan Lingkungan - Nikmatul Udzmah; Dian Tauhidah; Ndzani Latifatur Rofi’ah (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
Rapid environmental changes demand an increase in environmental literacy and eco-anxiety management among students. Environmental literacy is important for students because it can form concern for environmental problems, while eco-anxiety is only at a certain level, so that students can be motivated to take real action in protecting the environment. The results of pre-research on environmental literacy and eco-anxiety of students showed a low category. This study aims to analyze the effect of implementing the Project Based Learning (PjBL) model integrated with ecopreneurship on the level of environmental literacy and eco-anxiety of students on environmental change material in class X of high school. This type of research is a quasi-experiment with a nonequivalent control group design and a purposive sampling technique in selecting samples. The samples used were X-4 as the experimental class and X-5 as the control class. The results of the study show that the implementation of PjBL integrated with ecopreneurship has a significant effect on environmental literacy and eco-anxiety, as evidenced by the One Way ANCOVA test which produces a significance value (2-tailed) (p<0.05).